(untitled) (Cardiovascular Journal, 2011)
Day by day with the experiences and advancement in technology angioplasty has become more refined with higher rate of success and lower rate of complications. In spite of these there remain some of adverse outcomes following procedure. To minimize procedural complications and adversities were looked for evaluation of high risk features. Percutaneous coronary intervention related mortality is directly related to the episode of coronary artery occlusion and is associated with pronounced left ventricular failure. The variables associated with increased mortality include type C lesion , advanced age, female gender, diabetes, ST segment elevated myocardial infraction ,prior myocardial infraction, multivessel disease, left main or equivalent coronary disease, a large area of myocardium at risk, preexisting impairment of left ventricular or renal function, post- percutaneous coronary intervention worsening of renal function, and collateral vessels supplying significant areas of myocardium that originate distal to the segment to be dilated. Key words: Predictors of coronary intervention, Coronary artery disease DOI: http://dx.doi.org/10.3329/cardio.v1i1.8216 Cardiovasc. j. 2008; 1(1) : 72-77